E Efektivitas Rosuvastatin Dan Pravastatin Sebagai Anti-Dislipidemia Pada Tikus JANTAN - Furqan, Rizqi Nur; Nugraha, Dyan Fitri; Hakim, Ali Rakhman; Saputri, Rina; Komaliya, Risyda (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: Dyslipidemia is a disease that can have a negative impact on human health. Dyslipidemia treatment has 3 levels based on intensity, namely disease with high intensity, medium intensity, and low intensity. In this study, the drugs used were Pravastatin and Rosuvastatin, both of which were of medium intensity. Objective: Knowing the comparison of the effectiveness of the drugs Rosuvastatin and Pravastatin as anti-dyslipidemia in rats. Methods: The research method used in this study is True Experimental. The research design used in this study was the posttest only control group, namely by taking samples after being given the drugs Rosuvastatin and Pravastatin, so that it would be seen the effectiveness of the treatment given to the group of rats tested. Results: Rosuvastatin can lower LDL cholesterol better than Pravastatin because rosuvastatin has the highest binding interaction with HMG-CoA reductase, resulting in the strongest inhibition of cholesterol synthesis of all other statin groups. Pravastatin has the ability to lower LDL. From the results of the average values of the two statin class drugs, Rosuvastatin has a better average value than Pravastatin, but the statistical results can be concluded that there is no significant difference from the 0.5% Na CMC control to Rosuvastatin compared to Pravastatin. Conclusion: The statin class drug Rosuvastatin has better effectiveness than Pravastatin.